Linking methane rate to gas transport parameters of final soil cover at the Quezon City controlled dumping facility (Payatas dumpsite) - Phetyasone Xaypanya
Municipal waste disposal site such as landfills are known to be a significant source of methane gas emissions to the atmosphere. The knowledge on the physical, chemical, and biological process of fate and transport of landfill gases leads to a scientific/engineering based evaluation of risk associated with landfill gas and to a risk-based corrective measure that can be implemented at a waste landfill site. To estimate the methane emission from a landfill, an accurate description of the gas diffusive and convective transport parameters in the final soil cover are needed in addition to age, nature and composition, moisture conditions, and gas transport parameters in the waste layer. In this study, methane concentration and methane emission rates measured at the approximately 2500 m2 portion of the closed Payatas Controlled Dumpsite on Quezon City, Philippines. Also, the bulk density, particle density, soil pH, soil EC, and field water content were measured on selected points along two field transects and along three approximately 120 cm-deep profiles where high and low methane concentrations were observed. In addition, soil-gas diffusitivity (Dp/D0, where Dp is the soil-gas diffusion coefficient in m2 s-1 and D0 is the gas diffusion coefficient in free air in m2 s-1), and air permeability (ka) at field moisture conditions were measured on intact core samples collected at one of the transects and at various depths along the three soil profiles. Results showed the average methane emission rate in almost one year period is 887.22 g CG4 m-2 d-1 with range from 2 to 3297 g CH4 m-2 d-1. The observed soil-gas diffusitivity of the landfill cover (Dp/D0) at field water condition is very low and less than 0.1 and the range of values for ka is 0.77 um2 to 50.27 um2, respectively while the range of field water content is 0.39 to 0.49 cm3 cm-3 (soil) with 0.35-0.53 m3 m-3 range of soil total porosity.